Longitudinal static stability of a blended wing-body unmanned aircraft with canard as longitudinal control surface / Rizal E. M. Nasir, Wahyu Kunjoro and Wirachman Wisnoe - E.M. Nasir, Rizal; Kunjoro, Wahyu; Wisnoe, Wirachman (UiTM Press, 2012)
Blended wing-body (BWB) aircraft, while having good aerodynamic efficiency, is hampered with issues related to its flight stability and control. To ensure longitudinal stability, a control canard is incorporated on Baseline-II E-2 BWB design. Mathematical representations of aerodynamic characteristics and stickfixed trim flight stability, and analyses on the influence of some parameters to trim flight of this BWB aircraft with a control canard are highlighted and discussed. Baseline-II E-2 BWB aircraft is statically stable in longitudinal direction. However, this is true only for flight within low angles of attack. Mathematical models of trim flight parameters established here produces plots that have good agreement with plots of trim flight parameters found directly from wind tunnel experiments. Large static margin demands large positive canard angle for trim flight while agility can be achieved by moving the CG closer to aircraft’s neutral point. The best static margin for Baseline-II E-2 BWB is chosen based on the best lift-to-drag ratio attainable during trim flight.